Organizational Culture, Justice, Dehumanization and Affective Commitment in French Employees: A Serial Mediation Model - Jean-Félix Hamel; Fabrizio Scrima; Lucie Massot; Benoît Montalan (Europe's Journal of Psychology, 2023)
The instrumentality of employees can be considered a common feature of the modern workplace. To investigate the influence of this instrumentalizing culture on organizational performance on the individual level, we tested whether perceived clan values (according to the Competing Values Framework) could explain affective commitment directly and indirectly through perceptions of organizational justice and organizational dehumanization in employees. Using the PROCESS macro, we tested a corresponding serial mediation model in a convenience sample of 306 French employees. Although employees who perceived a lack of clan values were less committed, the observed indirect effect was greater. Our findings highlight the role of perceived organizational culture in influencing affective commitment and how perceived justice and dehumanization may explain part of this relationship. This research also contradicts widespread beliefs stating dehumanizing strategies are universally beneficial in terms of organizational efficiency. Limitations and directions for future research are discussed.